Impact Of Innovations On The Growth And Performance Of Micro, Small And Medium Enterprises In India (International Journal of Food and Nutritional Sciences, 2022)
Schumpeter effect suggests that higher levels of entrepreneurship reduce unemployment and contribute to socio-economic development. Micro, Small and Medium Enterprises (MSME) have emerged as a significant and dynamic sector in the Indian economy, providing large employment with low capital costs and contributing significantly to the country's socio-economic development. MSMEs account for 45% of manufacturing output and 40% of total exports, employing about 60 million people in over 26 million units. They offer opportunities for self-employment and wage employment outside the agriculture sector, contributing to economic growth, inclusive society, gender and social justice, and environmentally sustainable development. The MSME development Act, 2006 introduced the concept of enterprise and classification based on investments into Micro, Small and Medium Enterprises. The growth rate of MSMEs has increased from 5.70% in 2002-03 to 10.40% in 2009-10, with an annual growth rate of 8.68% to 13%. However, there is a wide gap of credit for this sector due to its heterogeneous and unorganized nature. Alternative sources of finance are needed for growth in areas such as nano technology, biotechnology, aerospace, defence applications, and homeland securities.